2023
DOI: 10.3390/synbio1020012
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Serine Integrases in Synthetic Biology over the Past Decade

Fang Ba,
Yufei Zhang,
Luyao Wang
et al.

Abstract: Serine integrases are emerging as one of the most powerful biological tools for biotechnology. Over the past decade, many research papers have been published on the use of serine integrases in synthetic biology. In this review, we aim to systematically summarize the various studies ranging from structure and the catalytic mechanism to genetic design and interdisciplinary applications. First, we introduce the classification, structure, and catalytic model of serine integrases. Second, we present a timeline with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 134 publications
(243 reference statements)
0
2
0
Order By: Relevance
“…Integrated DNA is more stable in the host and reduces the need for antibiotic-based selection. Serine integrase and recombinase-based systems can remove host range limitations of a replicating plasmid and the efficiency of native homologous recombination to evaluate heterologous genes and pathways (Ba et al., 2023 ; Elmore et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Integrated DNA is more stable in the host and reduces the need for antibiotic-based selection. Serine integrase and recombinase-based systems can remove host range limitations of a replicating plasmid and the efficiency of native homologous recombination to evaluate heterologous genes and pathways (Ba et al., 2023 ; Elmore et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of the evolutionary position of this phage have shown that it may have originated from a P2-type temperate phage and nonproliferative homologous fragments of this phage exist in several A. hydrophila strains, as phiO18P is also a temperate phage and has a ORF of phage major capsid protein of the P2 family in its genome ( 67 ). Integrase drives recombination between the phage and specific attachment sites on the host chromosome known as attP and attB during the integration process ( 68 ), while holin can accumulate in the bacterial cytosol and eventually penetrate the peptidoglycan layer, and can achieve control of the lytic cycle through self-regulation of its concentration ( 69–71 ). This result suggests that the genome of phiA051 is characterized by both temperate phage and virulent phage.…”
Section: Discussionmentioning
confidence: 99%